2004
DOI: 10.1029/2003gl018741
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis of Amazon hydrological regime variability

Abstract: [1] Wavelet analysis allows for an insightful examination of the temporal variability of Amazon basin hydrology and highlights intermittent interannual and interdecadal fluctuations. Two main conclusions arise. Interannual fluctuations appear as closely related to equatorial Pacific forcings whereas 15-year and bi-decadal fluctuations are strongly correlated with Pacific and tropical Atlantic long term forcings. The 1970's climate shift affects the Amazon basin, implying a correlation between both NATL and SOI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 27 publications
4
37
0
2
Order By: Relevance
“…Wang and Eltahir (1999), Tawfik (2003) and Eldaw et al (2003) have corroborated the Nile discharge-SOI association. Labat et al (2004Labat et al ( , 2005 using wavelet techniques showed that the Amazon, Parana, Orinoco and Congo river flows were influenced by the SOI on a 3-6-year time-scale in keeping with the earlier study of Amarasekera et al (1997), while longer term variability was influenced by a combination of the Pacific Decadal Oscillation and the North Atlantic Oscillation. Whitaker et al (2001), concentrating on the Ganges, found a relatively strong relationship at the 95% significance level between annual river flow and indices of the extremes of El Niño-Southern Oscillation (ENSO) and also whether the trend of the SOI was increasing or decreasing, suggesting that there existed a basis for prediction.…”
Section: Introductionsupporting
confidence: 83%
“…Wang and Eltahir (1999), Tawfik (2003) and Eldaw et al (2003) have corroborated the Nile discharge-SOI association. Labat et al (2004Labat et al ( , 2005 using wavelet techniques showed that the Amazon, Parana, Orinoco and Congo river flows were influenced by the SOI on a 3-6-year time-scale in keeping with the earlier study of Amarasekera et al (1997), while longer term variability was influenced by a combination of the Pacific Decadal Oscillation and the North Atlantic Oscillation. Whitaker et al (2001), concentrating on the Ganges, found a relatively strong relationship at the 95% significance level between annual river flow and indices of the extremes of El Niño-Southern Oscillation (ENSO) and also whether the trend of the SOI was increasing or decreasing, suggesting that there existed a basis for prediction.…”
Section: Introductionsupporting
confidence: 83%
“…Gaucherel (2002) detected and explained the 'Short March Summer' meteorological phenomenon over the Guyana Shield using wavelet analysis of the Guyanian watershed discharge series. Labat et al (2004) proposed a wavelet analysis of the annual rainfall over the Amazon basin and of the annual regime of the Amazon discharge at Obidos, in relationship to climatic drivers.…”
Section: The Wavelet Transform In Geosciencesmentioning
confidence: 99%
“…Earlier applications of wavelets to discharge time series already allows to detect climatic oscillation [21,23,27]. The reader is referred to Ghil et al [12] and Labat et al [25] for a more complete bibliography on the applications of wavelets in geosciences.…”
Section: Overview Of Wavelet Analysismentioning
confidence: 98%